2004
DOI: 10.1016/j.jacc.2004.03.065
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of AT1-antagonism and angiotensin-converting enzyme inhibition on markers of inflammation and platelet aggregation in patients with coronary artery disease

Abstract: Angiotensin-converting enzyme (ACE) inhibition and angiotensin II type 1 receptor (AT1) blockade reduced serum MMP-9 protein/activity to a similar extent, and only AT1 blockade reduced hsCRP, IL-6, and platelet aggregation in patients with CAD. Thus, AT1-blockade appears to exert stronger systemic anti-inflammatory and anti-aggregatory effects compared with ACE inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(146 citation statements)
references
References 41 publications
5
133
1
7
Order By: Relevance
“…We have recently demonstrated that inflammatory urine biomarkers also increase in response to acute clamped hyperglycaemia; however, the role of the RAAS in mediating this response and the reversibility of this phenomenon was unknown. We hypothesised that blockade of the RAAS would mitigate the effect of clamped hyperglycaemia on urinary cytokines/chemokines [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that inflammatory urine biomarkers also increase in response to acute clamped hyperglycaemia; however, the role of the RAAS in mediating this response and the reversibility of this phenomenon was unknown. We hypothesised that blockade of the RAAS would mitigate the effect of clamped hyperglycaemia on urinary cytokines/chemokines [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer was the only biomarker showing a significant difference between fosinopril intervention (median 0.32 μg/mL, interquartile range 0.22-0.52 μg/mL) and placebo (median 0.29 μg/mL, interquartile range 0.20-0.47 μg/mL, P = .007). From analysis of their data authors concluded that ACE inhibition does not significantly modify major biomarkers of inflammation, hemostasis, and endothelial function, although further studies should have confirmed the possible effect of ACE inhibitors on the fibrinolysis pathway [234]. These really discouraging findings might be specifically related to the ACE inhibitor molecule adopted in the TRAIN study (ie, fosinopril).…”
Section: Perindopril Vs Enalapril (Vs Placebo)mentioning
confidence: 97%
“…Schieffer et al (2004) [234] In patients with CAD and arterial hypertension six to eight weeks after coronary angioplasty, after 3 months of treatment, both enalapril and irbesartan enhanced serum IL-10 levels and reduced serum MMP-9 protein and MMP-9 activity. Only IRB reduced serum IL-6 and hsCRP levels significantly compared with baseline (p < 0.01), whereas ENAL did not.…”
Section: Enalapril (Vs Irbesartan)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have suggested that Ang II via its AT1R plays an important role in triggering inflammatory cardiovascular injury (4,5). Indeed, the cardioprotective effects of AT1R blockade are related to reduced myocardial inflammation in patients with MI (9). Accumulating experimental evidence from AT2R knockout mice or from rats under AT2R agonists further indicates that AT2R, which may be exposed to enhanced Ang II level after AT1R blockade, afford protection against MI-induced cardiac injury (5,10).…”
mentioning
confidence: 98%